1990
DOI: 10.1080/00071669008417240
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of zinc in egg yolk, ovarian follicles and organs after forced resting by high dietary zinc

Abstract: 1. Eighteen Warren SSL hens of 71 weeks of age were forced-moulted by ad libitum feeding of a high-zinc diet (10,000 ppm zinc for 2 days followed by 5,000 ppm zinc-supplement diet for 4 days). From the start of the treatment, eggs were collected and 3 hens were slaughtered on days 0, 2, 3, 4, 5 and 6 of the study. 2. Zinc analyses were carried out on the different components of the eggs and on liver, pancreas, kidney, different yolky follicles of the ovary and various segments of the oviduct. 3. Seven-, six- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The high zinc concentration in egg yolk at peak of the second production cycle in the zinc-induced molted group resulted from zinc supplementation during the molting period. Similar results have been reported by Verheyen et al (1990) that zinc-induced molting (zinc supplementation 10 000 ppm for 2 days and 5000 ppm for 4 days) elevates egg yolk zinc concentration. However, in the current study, the concentration of egg yolk zinc was only elevated at peak of the second production cycle in zincinduced molted group.…”
Section: Egg Yolksupporting
confidence: 90%
See 2 more Smart Citations
“…The high zinc concentration in egg yolk at peak of the second production cycle in the zinc-induced molted group resulted from zinc supplementation during the molting period. Similar results have been reported by Verheyen et al (1990) that zinc-induced molting (zinc supplementation 10 000 ppm for 2 days and 5000 ppm for 4 days) elevates egg yolk zinc concentration. However, in the current study, the concentration of egg yolk zinc was only elevated at peak of the second production cycle in zincinduced molted group.…”
Section: Egg Yolksupporting
confidence: 90%
“…However, Kaya et al. (2001) and Verheyen et al. (1990) reported that egg albumin zinc concentration did not increase after dietary zinc supplementation and zinc‐induced molting respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc tends to accumulate in the reproductive system when birds are induced to molt by zinc feeding (McCormick and Cunningham 1984;Verheyen et al 1990). However, the consequence of high levels of zinc accumulation in the reproductive tissues during the induced molting is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Verheyen et al (1990) and Stahl et al (1986) reported considerable increase of zinc content in egg yolk after adding zinc supplement to the feed, while Skřivan et al (2005) and Kaya et al (2009) reported decrease of zinc content in egg yolk after adding supplements in feed. Palafox & Ho (1980) reported that adding 20 000 pg Zn/g for five days decreased the zinc content and egg production for a few days.…”
Section: Resultsmentioning
confidence: 92%